2018
DOI: 10.1021/acs.jproteome.7b00846
|View full text |Cite
|
Sign up to set email alerts
|

Cord Blood Metabolic Signatures of Birth Weight: A Population-Based Study

Abstract: Birth weight is an important indicator of maternal and fetal health and a predictor of health in later life. However, the determinants of variance in birth weight are still poorly understood. We aimed to identify the biological pathways, which may be perturbed by environmental exposures, that are important in determining birth weight. We applied untargeted mass-spectrometry-based metabolomics to 481 cord blood samples collected at delivery in four birth cohorts from across Europe: ENVIRONAGE (Belgium), INMA (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(76 citation statements)
references
References 64 publications
6
69
1
Order By: Relevance
“…Interestingly, very recently Robinson et al . 50 observed in line with our results a negative association between birth weight, indolelactic acid and PCs in a population based study. The additional effect of PE could be controlled by comparing results with small for gestational age, non-PE newborns.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, very recently Robinson et al . 50 observed in line with our results a negative association between birth weight, indolelactic acid and PCs in a population based study. The additional effect of PE could be controlled by comparing results with small for gestational age, non-PE newborns.…”
Section: Discussionsupporting
confidence: 93%
“…Also, we identified two sphingolipids (SM C16:1 and SM C18:1) to be both higher in females and positively associated with BMI z-score, possibly reflecting differences in body fat composition and physical development between boys and girls. Also, two of the lysophosphatidylcholines (lysoPC a C16:1, lysoPC a C18:1) associated with BMI z-score in this study have recently been shown to be correlated to infant birth weight [ 89 ]. Moreover, out of the 41 serum metabolites found to be associated with BMI z-score in our HELIX children cohort, 14 metabolites (including kynurenine, glutamate, lysoPC a C18:1, lysoPC a C18:2) have also previously been reported in the EPIC study in an adult population, where the Absolute IDQ p180 kit was also used [ 90 ], demonstrating that many serum metabolic associations with BMI observed in adulthood can also be found in childhood.…”
Section: Discussionmentioning
confidence: 99%
“…Sample extracts were analysed by LC-MS using a 1290 Binary LC system coupled with a 6550 quadrupole time-of-flight (QTOF) mass spectrometer equipped with a jet steam electrospray ionization source (Agilent Technologies, Santa Clara, CA, USA), as previously described [ 35 ]. In short, samples were ordered randomly in the batch.…”
Section: Methodsmentioning
confidence: 99%